KINERJA PEMERIKSA PAJAK: TIGA VARIABEL PENJELAS PEN-CAPAIAN TARGET PAJAK OPTIMAL - Santuo Santuo (Jurnal Administrasi Negara, 2019)
Tax audit success is determined by performance of tax auditors. Therefore, to achieve optimal tax audit results, some efforts are needed to increase performance of tax auditors. Performance of tax auditors is influenced by several factors, including professionalism, work experience and organizational commitment of tax auditors. Several previous studies have shown that professionalism, work experience and organizational commitment influence performance of tax auditors. But there are also some previous studies show professionalism, work experience and organizational commitment do not influence performance of tax auditors. This study aims to determine the effect of including professionalism, work experience and organizational commitment on performance of tax auditors at Bulukumba Small Tax Office. The Population of this study are 37 tax auditors at Bulukumba Small Tax Office. The number of samples is determined by total sampling technique, which is taking all the population of 37 respondents. The data collection technique is questionnaire. Data analysis used is through multiple linear regression analysis with partial and simultaneous hypothesis tests. The results indicate that there is a positive and significant influence on professionalism, work experience and organizational commitmentto performance of tax auditors. This means that performance of tax auditors at Bulukumba Tax Office is generally influenced by professionalism, work experience and organizational commitment of tax auditors and the others is influenced by other factors not included in this research model